Relationship of squat one repetition maximum to weight throw performance among elite and collegiate athletes - Judge, L. W.; Bellar, D.; Turk, M.; Judge, M.; Gilreath, E.; Smith, J. (International Journal of Performance Analysis in Sport, 2011)
Weight room 1 repetition maximums (1RM) have been shown to be associated with performance in the throwing events. The purpose of this study was to investigate the primary variables that contributed to maximum throwing distance in the indoor weight throw event in track and field. A survey instrument was developed to collect data regarding national level collegiate weight throwers in the United States. Bivariate correlations for weight throw personal best and squat 1RM revealed significant correlations for both the male (r=0.642, p<0.001) and female participants (r=0.799, p<0.001). The height of the female athletes was also significantly correlated to weight throw personal best (r=0.710, p<0.001); however, height was not significantly correlated to personal best among male participants (r=0.173, p=0.361). Furthermore, the results may provide some insight into the obstacles and barriers limiting the development of US weight throwers.